Pharmacokinetics, safety, and tolerability of single and multiple-doses of pinocembrin injection administered intravenously in healthy subjects - Cao, Guoying; Ying, Pengyue; Yan, Bei; Xue, Wei; Li, Kexin; Shi, Aixin; Sun, Taohua; Yan, Jiling; Hu, Xin (Journal of ethnopharmacology, 2015)
Pinocembrin is the most abundant flavonoid in propolis. Preclinical studies have suggested that pinocembrin protects rat brain against oxidation and apoptosis induced by ischemia–reperfusion both in vivo and in vitro. To investigate the safety, tolerability and pharmacokinetics of a new neuroprotective agent, pinocembrin. A double-blind, placebo-controlled, randomized study was carried out in 58 healthy subjects. Single ascending doses of pinocembrin (20–150mg) were evaluated in 5 cohorts. Multi-dose was studied at pinocembrin 60mg. Pinocembrin was well tolerated. No serious adverse events occurred. No subjects were discontinued because of a treatment emergent AE. Treatment related adverse event was acute urticaria. Two subjects in 150mg cohort developed grade II urticaria during the study. One subject discontinued after 3 days at 60mg bid because of diarrhea. In the single-dose study, the mean peak plasma pinocembrin concentration was obtained at the end of the 30-min infusion. The Cmax ranged from 0.28μgmL−1 to 2.46μgmL−1. AUC (0,∞) ranged from 10.34μgmL−1min to 89.34μgmL−1min. The T1/2 was similar across 5 dose groups, ranging from 40 to 55min. Both urinary and feces excretion levels of pinocembrin were extremely low and similar among each dose groups, with mean values ranging from 0.07% to 0.17% and 0.94% to 1.94% of the administered dose, respectively. Linear increases in Cmax and AUC(0,∞) were observed. The pharmacokinetics of pinocembrin in multiple-dose was similar to those observed in the single-dose study, with no evidence of accumulation. Both urinary and feces excretion levels of pinocembrin were extremely low. Pinocembrin displayed linear plasma pharmacokinetics over the dose range, 20–150mg and was well tolerated up to 120mg day−1 when administered intravenously to healthy adults. No major safety concerns were identified that would preclude further clinical development of pinocembrin injection. [Display omitted]